The Influence of Jumping and Throwing Park Games on Students’ Basic Motor Skills - Komala Noor Herdiany; Helmy Firmansyah; Teten Hidayat (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the effect of jumping and throwing park games on improving basic motor skills of junior high school students. The research method used is an experiment with a pretest-posttest control group design. The sample consisted of two classes, each consisting of 30 students, divided into experimental and control groups. The instrument used refers to the Test of Gross Motor Development (TGMD-2) to measure jumping, throwing, and balance abilities. The results of the analysis showed that there was a significant increase in the post-test results of the experimental group compared to the control group (p = 0.000). Jumping and throwing park games have proven effective in integrating locomotor and manipulative movements through a fun play approach, thereby increasing students’ motivation and active participation in physical education learning. These findings indicate that learning media designed according to the characteristics of student development can make a real contribution to improving motor skills. Therefore, the use of this media is recommended as an alternative learning strategy that is educational and fun in the school environment.